Analysis of Physical Performance and Physiological Parameters of Futsal FIKK UNM Team - Saleh, M. Sahib; Saleh, Muh. Syahrul; Syafir, Muh. Isnawan; Syam, Asry; Syahruddin, Syahruddin (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
The game of futsal has an important role in improving the body's endurance system, because during the game, players are required to move with high intensity in various directions on the field continuously, which requires optimal physical condition. The FIKK UNM Makassar futsal team has experienced a significant decline in achievement in the past year, so an in-depth study is needed to maintain and improve team performance. This study aims to identify the physical condition of the futsal team based on the standards set by the Indonesian National Sports Committee (KONI). The research was conducted at the FIKK UNM Makassar field and the Laboratory of the Faculty of Sport and Health Sciences. The research sample consisted of all members of the futsal team, as many as 12 people, who participated voluntarily. The measurement instruments used include the Multistage Test to measure cardiorespiratory endurance, Leg Dynamometer to measure leg muscle strength, 50 meter run to measure speed, Shuttle Run Test to measure agility, and Vertical Jump to measure leg muscle explosive power. Data were analyzed using cumulative percentage. The results showed that aerobic endurance was in the good category (66.7%); leg muscle strength in the good category (58.3%); speed in the good category (66.7%); agility in the good category (58.3%); and leg muscle explosive power in the good category (75%). In conclusion, the overall physical condition of the FIKK UNM Makassar team is in the good category, although some physical components require improvement.